Estudio de factibilidad para la exportación de café verde desde la finca villa rosal hacia el mercado Europeo (2021)
Nowadays, Colombian economy growth is highly correlated to coffee production, it has been one of the main sources of foreign exchange, for example, in the 70’s coffee represented more than 50% of the total amount of exportations. Also, in the last years consumption and exportation has been growing in countries such as Japan, The United States, Belgium, Netherlands, among others. Coffee has plenty benefits, and it is one of the most consumed beverages in the world. Its chemical composition is determined by the variety, plantation altitude, climate and agronomic changes. Huila’s department has been recognized as the largest coffee producer in the country, more than 53% of its exportations are due to coffee. Therefore, the viability of exporting green coffee to Europe’s market from Villa Rosal farm located in Palermo-Huila, will be evaluated by the feasibility study, as there are no coffee exporting companies in this area.